The Use of MAGEC Growing Rods as a Temporary Distraction Rod in Severe Kyphoscoliosis: A Case Report. Issue 1 (April 2016) - Smith, John; Morgan, Jessica
Background: The acute correction of severe spinal deformity can be associated with significant neurologic risk. Halo traction can be used as a method to slowly correct deformity while allowing for close neurologic monitoring during correction. However, this typically requires a prolonged hospital stay and significant costs. Methods: This case reports using a magnetically controlled growing rod (MCGR) to continue correction of a severe spinal deformity after an initial period of halo traction to allow for safe correction a severe kyphoscoliosis. Results: The patient is a female child, adopted from Ethiopia, with an estimated age between 10–13 years. She presented with a severe kyphoscoliosis measuring greater than 135 degrees. She is otherwise healthy. An MRI showed no abnormalities of the spinal cord. Due to the severity of her curve, we elected to use halo-gravity traction for 4 weeks. During that time, she gained 7 inches in height and her curve improved to 100 degrees. To continue her correction, we then placed a Magnetic Growing rod from T1-L3/4, and distracted on a monthly basis for 6 months; resulting in correction of her curve to 80 degrees. The patient then underwent removal of the MCGR, and had definitive posterior spinal instrumentation and fusion from T2-L4 with apical Ponte osteotomies. Her scoliosis corrected to 47 degrees and her kyphosis to 42 degrees. She was left with a visible cervical deformity that is currently asymptomatic. Conclusion: Multiple authors have reported the use of traction as part of the treatment of severe scoliosis as a means to reduce neurologic risk during deformity correction. 1, 2 Surgical placement of temporary distraction rods have also been reported as part of a staged correction of severe scoliosis but is associated with loss of neuromonitoring signals in 41% of patients. These changes were reversible if the temporary traction was reversed. Cheung et al reported the use of a MCGR in a girl with severe spinal deformity where distractions were made daily for 2.5 months prior to definitive correction. 3 The MCGR offers a safe option as a temporary distraction rod that can be lengthened gradually on an outpatient basis. This allows for neurological monitoring during gradual correction of the curve in anticipation of definitive correction. References Sponseller PD, Takenaga RK, Netown P, et al. The use of traction in the treatment of severe spinal deformity. Spine 2008;33:2305–2309 Buchowski JM, Bhatnagar R, Skaggs DL, Sponseller PD. Temporary internal distraction as an aid to correction of severe scoliosis. J Bone Joint Surg Am 2006;88:2035–2041 Cheung JP, Samartzis D, Cheung KM. A novel approach to gradual correction of severe spinal deformity in a pediatric patient using the magnetically-controlled growing rod. Spine J 2014;14:e7–e13